Analisis Peran Komunikasi Interpersonal terhadap Produktivitas Kerja Karyawan di PT. Yakult Indonesia Persada Cabang Ciranjang - Vesti Nadari Artisti; Devi Maria Saadah (Lembaga Pengembangan Kinerja Dosen, 2025)
The objective of this scientific research is to analyze the role of interpersonal communication in employee work productivity at PT. Yakult Indonesia Persada, Ciranjang Branch. In an organizational context, the quality of human resources greatly influences success, which can be observed through the way individuals communicate to achieve shared goals. Effective interpersonal communication encompasses five key indicators: openness, empathy, support, positive attitude, and equality. This study adopts a descriptive qualitative approach, with data collected through interviews and observations of employees in the workplace. The findings of this research indicate that good communication can foster a harmonious and collaborative work environment, which in turn enhances work productivity. The study reveals that the principles of effective interpersonal communication contribute to improved work enthusiasm and efficiency.